2007
DOI: 10.1111/j.1440-1746.2006.04659.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of hepatic fibrogenesis

Abstract: Liver fibrosis, a wound-healing response to a variety of chronic stimuli, is characterized by excessive deposition of extracellular matrix (ECM) proteins, of which type I collagen predominates. This alters the structure of the liver leading to organ dysfunction. The activated hepatic stellate cell (HSC) is primarily responsible for excess collagen deposition during liver fibrosis. Two important aspects are involved in mediating the fibrogenic response: first the HSC becomes directly fibrogenic by synthesizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
204
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(216 citation statements)
references
References 77 publications
6
204
0
3
Order By: Relevance
“…Hepatic fibrosis is usually initiated by hepatocyte damage, leading to recruitment of inflammatory cells, with subsequent release of cytokines and growth factors (Muriel, 2007a,b), which probably link the inflammatory and reparative phase of hepatic fibrosis, by activating hepatic stellate cells (HSC) (Parsons et al, 2007). Activated HSC are the main source of extracellular matrix production, and contribute to liver damage through expression of adhesion molecules and cytokines.…”
Section: Pyrrolidine Dithiocarbamate In Acute and Chronic Liver Damagementioning
confidence: 99%
“…Hepatic fibrosis is usually initiated by hepatocyte damage, leading to recruitment of inflammatory cells, with subsequent release of cytokines and growth factors (Muriel, 2007a,b), which probably link the inflammatory and reparative phase of hepatic fibrosis, by activating hepatic stellate cells (HSC) (Parsons et al, 2007). Activated HSC are the main source of extracellular matrix production, and contribute to liver damage through expression of adhesion molecules and cytokines.…”
Section: Pyrrolidine Dithiocarbamate In Acute and Chronic Liver Damagementioning
confidence: 99%
“…Upon chronic injury, liver parenchyma is replaced by excess extracellular matrix (ECM) produced by activated hepatic stellate cells (HSC) and myofibroblasts, resulting in cirrhotic remodeling, progressive functional impairment and-potentially-hepatocellular cancer (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking this pathway can inhibit HSC proliferation and ECM expression, leading to an improvement in patients with liver fibrosis [32] . Marra et al [33] showed that the activation of the PKC-PI3K-AKT signaling pathways promoted the mitosis and chemotaxis of HSC cells.…”
Section: Discussionmentioning
confidence: 99%